Obscure gastrointestinal haemorrhage of small-bowel origin. Issue 6431 (2nd June 1984) - Thompson, J N; Hemingway, A P; McPherson, G A; Rees, H C; Allison, D J; Spencer, J
Abstract : The records of 37 patients investigated for obscure gastrointestinal haemorrhage originating from the small bowel were reviewed retrospectively. Bleeding was caused by Meckel's diverticula in eight cases, smooth muscle tumours in seven cases, vascular anomalies in 14 cases, and other single lesions in eight cases. The lesions were identified by angiography in 18 patients, operation in 17, and barium follow through examination in two. Only one patient under 50 years of age had a lesion that would not have been found by careful laparotomy. Early laparotomy is advisable in patients aged under 50 with obscure gastrointestinal bleeding; expert selective angiography is recommended before operation in patients aged over 50 and those who have already undergone a laparotomy yielding negative results.